Entendendo a rua completa no Brasil: contribuições para implementação e abordagem do conceito - Balestrin, Zamara Ritter (2021)
In the last decades, much of the work of researchers and urban planners has been pointing to a growing and necessary paradigm shift in the public space of the city streets. This change refers to a new vision about the priorities of the street, to meet different purposes, uses and public rights of passage. Thinking of balancing these priorities, the Complete Streets movement presents itself as an alternative to contribute to this change, aiming to make the streets spaces with a greater diversity of modes, uses and activities. This research contains contributions to the understanding, dissemination and practice of Complete Streets initiatives in Brazil, based on a compendium of essential points about the concept, purposes and approaches of the movement. Therefore, the qualitative approach conducts research of an exploratory nature, supported by bibliographical (books, articles, theses and dissertations) and documentary surveys (news, data on projects, images and technical materials) on the theme Complete Streets. This study contextualizes Complete Streets overview in Brazil, and the process of transitioning the ideas of this movement - from the United States of America (USA) - for the brazilian scene. To broaden the discussion, the work presents contributions through a semi-structured interview with two WRI Brazil collaborators - the institute responsible for spreading the concept in the country. In general, this synthesis seeks to provide a basis for new studies and initiatives in the social, political, technical and academic spheres that aim to build more humane and inviting spaces.